Low complexity predictive torque control strategies for a three‐level inverter driven induction motor. Issue 5 (1st May 2017) - Habibullah, Md.; Lu, Dylan Dah‐Chuan; Xiao, Dan; Fletcher, John E.; Rahman, Muhammed Fazlur
Abstract : Iterative and complex prediction loop is a challenge for the implementation of finite‐state predictive torque control (FS‐PTC) of motor drive. The complexity is due to the complex torque calculations, number of available voltage vectors (which are called as prediction vectors), and weighting factor tuning for torque and flux errors in the cost function. One way to reduce the complexity is an equivalent reference stator flux vector calculation (RSFVC) from torque and flux references, which also solves the problem of weighting factor tuning. Along with a new stator flux based RSFVC technique, a reduced number of prediction vectors are proposed in this study to reduce the number of iteration of the prediction loop. The position of the stator flux and sign of the stator flux‐error are considered to lessen the number of prediction vectors. Hence, the implementation challenges of FS‐PTC algorithm are overcome. The performance of the proposed technique is investigated for two types of RSFVCs: one is based on the stator flux, and another one is based on the rotor flux. Experimental results verify that the proposed low complexity FS‐PTC strategies retain the advantages of a conventional FS‐PTC.